Odpowiedzi

Najlepsza Odpowiedź!
2010-04-11T13:04:37+02:00
1. 3(x+3)=2(x+4)+x+1
3x+9=2x+8+x+1
3x-2x-x=8+1-9
0=0
równanie tożsamościowe

2. 4(3x+2)+5(2x+3) = -(2x+13)
12x+8+10x+15=-2x-13
12x+10x+2x=-13-8-15
24x=-36
x=-1,5


Proszę:)
2010-04-11T13:04:41+02:00
3(x+3)=2(x+4)+x+1
3x+9=2x+8+x+1
x+9=9+x
0=0


4(3x+2)+5(2x+3) = -(2x+13)
12x+8+10x+15= -2x-13
24x=-13-8-15
24x=-36
x= -1,5
2010-04-11T13:06:07+02:00
1. 3[x+3]=2[x+4]+x+1
3x+9=2x+8+x+1
3x-2x-x=-9+8+1
0x=0
2 . 4[3x+2]+5[2x+3]=-[2x+13]
12x+8+10x+15=-2x-13
12x+10x+2x=-8-15-13
24x=-36//24
x=-1,5

prosze